2015
DOI: 10.1194/jlr.m060392
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive products formed in humans from fish oils

Abstract: The clinical cardiovascular utility of a diet rich in fi sh oils, particularly EPA and DHA, has been debated over the past 50 years ( 1-3 ). Large clinical outcome trials, such as the open-labeled GISSI-Prevenzione ( 4 ) or JELIS ( 5 ) studies, supported the notion that fi sh oil supplements confer therapeutic benefi t on patients with cardiovascular disease. However, an overview analysis of results of more than 50 randomized controlled trials and cohort studies addressing this question yielded equivocal resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 62 publications
(46 reference statements)
6
82
0
Order By: Relevance
“…Despite the capacity-related feature of this assay, with provocation by inflammatory stimuli, only modest amounts of LXA 4 and RvE1 were evident, while most specialized proresolving mediators were not detected. We and others have also largely failed to detect endogenous production of these mediators in plasma or urine (37, 38) and failed to relate alterations in specialized proresolving mediator formation in vivo in response to the evocation of inflammation with LPS or its resolution or the dose-dependent provision of their theoretical substrate (38). …”
Section: Discussionmentioning
confidence: 99%
“…Despite the capacity-related feature of this assay, with provocation by inflammatory stimuli, only modest amounts of LXA 4 and RvE1 were evident, while most specialized proresolving mediators were not detected. We and others have also largely failed to detect endogenous production of these mediators in plasma or urine (37, 38) and failed to relate alterations in specialized proresolving mediator formation in vivo in response to the evocation of inflammation with LPS or its resolution or the dose-dependent provision of their theoretical substrate (38). …”
Section: Discussionmentioning
confidence: 99%
“…In the same report, SPMs were measured before and after an intravenous bolus of endotoxin that was administered to six volunteers who had taken 5 g/day n-3 fatty acids for 8 weeks. The authors reported that PD1 and PDX were present in plasma in low picograms quantities, but were unaffected by fish oil or endotoxin [26]. The study failed to detect any SPMs in urine after high-dose fish oil supplementation [26].…”
Section: Specialized Proresolving Mediators In Humans and The Effect mentioning
confidence: 95%
“…The authors reported that PD1 and PDX were present in plasma in low picograms quantities, but were unaffected by fish oil or endotoxin [26]. The study failed to detect any SPMs in urine after high-dose fish oil supplementation [26].…”
Section: Specialized Proresolving Mediators In Humans and The Effect mentioning
confidence: 95%
See 1 more Smart Citation
“…One likely possibility is that dietary n-3 PUFAs, which serve as substrates for specific enzymes, are enhancing the production of pro-resolving lipid mediators [33]. Indeed, there is evidence in the literature to show that dietary n-3 PUFA supplementation can increase levels of pro-resolving lipid mediators, although there are some labs that question this possibility [34-36]. Furthermore, Phipps and co-workers have demonstrated that 17-HDHA, a hydroxylated DHA molecule, enhances the production of antibody secreting cells in vitro and in vivo [37, 38].…”
Section: Discussionmentioning
confidence: 99%